Estudio de factibilidad para la apertura de un centro de distribución de productos de nutrición de la empresa Herbalife S.A., en el cantón Quevedo año 2015 - Guanoquiza Toapanta, Nancy Maribel (2015)
This project aims to conduct a feasibility study for the opening of a distribution center nutrition products company "Herbalife" in the Canton Quevedo, 2015, the fundamentals related to the location and context of the problems analyzed , expected changes to the research and its objectives for the realization of this project methods of data collection techniques were applied, in which through a survey could determine the acceptance company will market and the following are applied: A market study, which determined the potential demand, product preferences they would like to acquire, and the reasons for their use, as well as the frequency of purchase thereof, and establish strategies for the promotion of products and media are through print, television and social networks. A technical study in which the place is located microenterprise, as its dimensions and different departments, was established the same will have an area for management, an area for customer service, an area of sale and another delivery. The initial investment is $26.897,77 which 26% is equity $ 6.993,42 while 74% will be funded by the National Development Bank or $ 19.904,35 five-year term and an interest rate of 11% anual internal rate of return of 82% and the net present value of the investment is $56.643,33 with a benefit cost ratio of $1,28 recovery time of investment is 1 years , 11 months and 4 days which indicates that the project is profitable.